DAMPAK PSIKOLOGIS ACNE VULGARIS PADA REMAJA DI LINGKUNGAN SOSIAL : SYSTEMATIC LITERATURE REVIEW - Vio Hardita, Firnanda; Annisa Fitriani; Nugroho Arief Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Acne vulgaris is a common skin condition experienced by adolescents and is often perceived merely as a physical problem, even though it can also lead to significant psychological and social impacts. Changes in appearance caused by acne may affect self-image, self-esteem, and social interactions during this vulnerable developmental stage. This study aims to comprehensively examine the psychological impact of acne vulgaris on adolescents within their social environment. The method employed was a Systematic Literature Review (SLR) using the PRISMA approach on 20 scientific articles published between 2020 and 2025 and retrieved from the Scopus, ScienceDirect, PubMed, and Google Scholar databases. The selected articles were analyzed using a mixed methods synthesis approach to integrate findings from quantitative, qualitative, and mixed-method studies. The results indicate that acne vulgaris has a significant psychological impact on adolescents, particularly in the form of body image disturbances, reduced self-esteem, social anxiety, psychological stress, and an increased risk of depression. In addition, social stigma and environmental pressure play a role in exacerbating adolescents’ psychological conditions and encouraging withdrawal from social interactions. These findings emphasize that acne vulgaris is a biopsychosocial condition that affects adolescents’ mental well-being and quality of life, highlighting the need for holistic management that addresses dermatological, psychological, and social aspects.